Swearing Expressions by Main Male and Female Characters in Night School Movie - Ningrum, Erna Elya; Netra, I Made; Primahadi Wijaya Rajeg, Gede (Udayana Journal of Social Sciences and Humanities; Vol 5 No 2 (2021): UJoSSH, September 2021, 2021)
The use of swearing expressions used by men and women indicates a difference. This difference occurs due to the stereotypes between sex and gender. In this study, the differences of language expressions used between men and women are investigated. Language expressions that are self-referenced are swear words as a form of expressing emotions. This study used a transformative mixed method and the data were taken from both main male character and female character of a film entitled " Night School ".  Based on these data, it is concluded that different conditions and situations affect the different types and motives of the occurrence of swear words as a form of language expression between men and women.